2021
DOI: 10.1161/jaha.120.018624
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulation Before Hospitalization Is a Potential Protective Factor for COVID‐19: Insight From a French Multicenter Cohort Study

Abstract: Background COVID‐19 is a respiratory disease associated to thrombotic outcomes with coagulation and endothelial disorders. Based on that, several anticoagulation (AC) guidelines have been proposed. We aimed to identify if AC therapy modifies the risk of developing severe COVID‐19. Methods and Results COVID‐19 patients initially admitted in medical wards of 24 French hospitals were included prospectively from February 26th to April 20th, 2020. We used Po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
59
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 51 publications
(66 citation statements)
references
References 35 publications
6
59
0
1
Order By: Relevance
“…Other studies have also evaluated patients diagnosed with COVID-19 to determine complication and mortality rates in patients with previous antithrombotic therapy [ 23 , 26 , 30 , 33 , 34 ]. Those studies included from 110 to 731 anticoagulated patients and from 98 to 912 patients on antiplatelet therapy, with highly heterogenous findings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies have also evaluated patients diagnosed with COVID-19 to determine complication and mortality rates in patients with previous antithrombotic therapy [ 23 , 26 , 30 , 33 , 34 ]. Those studies included from 110 to 731 anticoagulated patients and from 98 to 912 patients on antiplatelet therapy, with highly heterogenous findings.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a nationwide registry-based study, Fröhlich et al found that hospitalized patients who received DOACs or VKA had better composite (all-cause mortality or need for non-invasive or invasive ventilation or extracorporeal membrane oxygenation) outcomes compared to those on antiplatelet therapy [ 33 ]. Chocron and colleagues found that AC therapy prior to hospitalization was associated with better clinical outcomes (ICU admission and/or in-hospital mortality) [ 34 ]. By contrast, Tremblay et al observed no improvement in all-cause mortality, time-to-mechanical ventilation, or need for hospitalization in either group (AC or AP) [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, no benefit was observed for therapeutic or prophylactic treatment started in hospital. 28 COVID-19 patients show frequent alterations of the coagulation system characterized by higher levels of D-dimer, reduced platelet count, and prolonged prothrombin time. More relevant changes seem to characterize subjects with a worse prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…correlated to a reduced risk of intensive care unit admission and/or death. Interestingly, no benefit was observed for therapeutic or prophylactic treatment started in hospital [28].…”
Section: Accepted Manuscriptmentioning
confidence: 97%